2005
DOI: 10.1093/hmg/ddi235
|View full text |Cite
|
Sign up to set email alerts
|

Alms1-disrupted mice recapitulate human Alström syndrome

Abstract: Mutations in the human ALMS1 gene cause Alström syndrome (AS), a progressive disease characterized by neurosensory deficits and by metabolic defects including childhood obesity, hyperinsulinemia and Type 2 diabetes. Other features that are more variable in expressivity include dilated cardiomyopathy, hypertriglyceridemia, hypercholesterolemia, scoliosis, developmental delay and pulmonary and urological dysfunctions. ALMS1 encodes a ubiquitously expressed protein of unknown function. To obtain an animal model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
176
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(192 citation statements)
references
References 33 publications
(45 reference statements)
16
176
0
Order By: Relevance
“…In our search to explain how deletion of the same gene could produce a nearly opposite phenotype in two different laboratories, we surveyed expression of genes near the Fabp1 locus and surrounding obesity-related QTLs, including some genes ( Alms1, Retstat, Aqp1 ) that have been implicated in metabolic adaptations and body weight maintenance (28)(29)(30)(31)(32)(33). No evidence was found for gene duplication or altered expression of modifi er genes in this region in our L-Fabp Ϫ / Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
“…In our search to explain how deletion of the same gene could produce a nearly opposite phenotype in two different laboratories, we surveyed expression of genes near the Fabp1 locus and surrounding obesity-related QTLs, including some genes ( Alms1, Retstat, Aqp1 ) that have been implicated in metabolic adaptations and body weight maintenance (28)(29)(30)(31)(32)(33). No evidence was found for gene duplication or altered expression of modifi er genes in this region in our L-Fabp Ϫ / Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
“…Deconvolution of the pool revealed that the mutated (mut) ALMS1 and C6ORF89 peptides within pool 2 were immunogenic ( Figure 4C). ALMS1 plays a role in ciliary function, cellular quiescence, and intracellular transport, 37,38 whereas C6ORF89 encodes a protein that interacts with bombesin receptor subtype 3 (involved in cell cycle progression and wound repair of bronchial epithelial cells).…”
Section: Detection Of Immunogenic Neoepitopes Personal To Cll Patientsmentioning
confidence: 99%
“…Bbs1-4, Bbs6-8, Bbs9, and Bbs11 are all expressed during mouse adipogenesis (76), suggesting they may play a role in the generation of fat tissue. Other ciliary proteins have also been implicated in this process, including retinitis-pigmentosa GTPase regulator interacting protein 1-like (RPGRIP1L), which localizes to the basal body (77) and whose expression is decreased in the adipose tissue of mutants for the adjacent FTO gene (78) and the Alström syndrome gene ALMS1, for which obese knockout mice have been generated (79,80). The ALMS1 protein, which localizes to the basal body (81,82), is expressed in the early phases of adipogenesis and may be involved in the conversion of preadipocytes to adipocytes (83).…”
Section: Molecular Mechanisms Underlying Ciliary Phenotypesmentioning
confidence: 99%